The Role of Discourse Practice in Students’ Writing at Bosowa University - Muliati; St. Asriati. Am; Dahlia D. Moelier; Syaila Nur Amaliyah; Tamra; Nurfaisah Sahib (Journal of English Language Teaching and Applied Linguistics, 2026)
Discourse practice plays a crucial role in shaping students’ writing development at Bosowa University through meaningful academic interaction processes. Students were involved in learning and analyzing the uses of language through discourse practice, which involved content, lexical cohesion, and grammatical range. This study aims to examine the effectiveness of discourse practice in writing abilities. This is a qualitative study involving 16 English language students in the second semester of the English language department in the academic year 2024/2025. The total sampling was used for one class. Data collection for this research used writing evaluation, questionnaires, and interviews as the research instruments. The research findings reveal that the role of discourse practice in writing is to help students write coherently. In three phases, students had consistent content, used relevant lexical cohesion, and demonstrated an appropriate grammatical range. Moreover, students were able to shape their writing, which helped them read it more closely, and, therefore, it was easily readable. Therefore, discourse practice plays a crucial role in developing the ability to write and use language. It is recommended that discourse practice be integrated to enhance students’ coherence, critical thinking, and the quality of their academic writing.